Sandflies (Diptera: Psychodidae) associated with opossum nests at urban sites in southeastern Brazil: a risk factor for urban and periurban zoonotic Leishmania transmission? - Cutolo, Andre Antonio (Instituto Oswaldo Cruz, Ministério da Saúde, 2014)
Sandflies associated with opossum nests are reported for the first time in the yards of residences located in the urban area of the municipality of Monte Mor, situated in the metropolitan region of Campinas, state of São Paulo, Brazil. Eleven specimens of Evandromyia cortelezzii and one of Evandromyia lenti were captured in two Didelphis albiventris nests. Ev. cortelezzii is considered a secondary vector species for the transmission of Leishmania (Viannia) braziliensis and Leishmania (Leishmania) infantum in the Neotropics. This association may contribute to the introduction, establishment and maintenance of urban and periurban zoonotic transmission outbreaks of Leishmania and should therefore be investigated further.